sec⁴ A − sec² A is equal to
(a)tan² A − tan⁴ A
(b)tan⁴ A − tan² A
(c)tan⁴ A + tan² A
(d)tan² A + tan⁴ A
Answers
Answered by
27
Answer:
sec⁴ A − sec² A is equal to (tan²A + tan⁴A)
Among the given options option (d) (tan²A + tan⁴A) is correct.
Step-by-step explanation:
Given : sec⁴ A − sec² A
sec⁴ A − sec² A
= sec²A(sec²A - 1)
[Taking sec²A common]
= (1 + tan²A) × tan²A
[∵ sec²θ = 1 + tan²θ & sec²θ - 1 = tan²θ ]
sec⁴ A − sec² A = (tan²A + tan⁴A)
Hence, sec⁴ A − sec² A is equal to (tan²A + tan⁴A)
HOPE THIS ANSWER WILL HELP YOU...
Answered by
26
SOLUTION
L.H.S
R.H.S
hence proved ☺️
Similar questions